Implementation halal product certification through self-declare program for MSEs products in Cirebon Regency - Muhimatul Umami; Shofwatun Nada; Nur Lulu Anisa (Journal of Community Service and Empowerment, 2023)
Cirebon is one of the regions of West Java which has around 54,306 MSMEs. However, currently, there are still many MSEs actors who don't understand the urgency of halal certification and incomprehensible how to apply for a halal certificate for their products. This community service activity aims to socialize and assist in applying for halal product certification for MSEs through the self-declaration program. The research method is Community Education through training and counselling conducted in the Pasaleman and Beber area with the category of food and beverage products. The data were used descriptive analysis. The results show that the mentoring participants gave a positive response to these activities, and MSEs received assistance in the practice of submitting halal products to the SIHALAL application. Some MSEs actors were able to apply for halal certification with the verification application status completed by National Fatwa Committee, LP3H, some were still in the draft submission and some had not yet submitted because business actors were more focused on product sales, so the time to complete the submission documents was limited. Furthermore, the community service team evaluates activities and monitors tracking periodically after submitting halal certification until release certificate halal product.